2019
DOI: 10.1177/1357633x19871746
|View full text |Cite
|
Sign up to set email alerts
|

Online teletherapy for chronic pain: A systematic review

Abstract: Objective A systematic review designed to evaluate the benefits of remote group pain management for persons with chronic pain was performed. Methods PubMed, EMBASE and PsychINFO databases were searched in April 2019. Eligible studies evaluated teletherapy for chronic pain based on set inclusion and exclusion criteria. Two reviewers independently screened eligible studies, assessed risk of bias and extracted data. Each study design was rated and study quality was assessed using an 11-point scale of methodologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 65 publications
0
41
0
Order By: Relevance
“…There has been an increased demand and recommendation to use remotely supported eHealth pain management services with the outbreak, which brings unique changes in service delivery of pain management. 18 , 25 A recent systematic review found that teletherapy and remote online cognitive behavioral therapy (CBT) strategies can be effective in improving quality of life among persons with chronic pain, 41 with 1 study suggesting that online group CBT may be as effective in improving coping among persons with chronic pain as in-person groups. 42 Such findings are promising, although additional research is needed to evaluate the impact of eHealth while recognizing the unique challenges created by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an increased demand and recommendation to use remotely supported eHealth pain management services with the outbreak, which brings unique changes in service delivery of pain management. 18 , 25 A recent systematic review found that teletherapy and remote online cognitive behavioral therapy (CBT) strategies can be effective in improving quality of life among persons with chronic pain, 41 with 1 study suggesting that online group CBT may be as effective in improving coping among persons with chronic pain as in-person groups. 42 Such findings are promising, although additional research is needed to evaluate the impact of eHealth while recognizing the unique challenges created by the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 Online pain management programs seem to hold promise, 29 particularly when patients have contact with healthcare providers, albeit remotely. 54 Online resources can disseminate pain education, and online training programs on pain self-management can be developed for healthcare professionals, those with pain, and their close others. 30,41,84 However, these novel digital interventions might not be accessible for all and may even put up new barriers to those who require them the most (eg, socially disconnected individuals with limited digital literacy).…”
Section: Responding To Social Threats Posed By Covid-19mentioning
confidence: 99%
“…In most pain management settings, telemedicine has been used in the form of video consultation, which mainly focuses on complaints that can be orally solved, such as palliative care and self-management skills. Some reviews have identified small to moderate reductions in pain, disability, and psychological symptoms in intervention groups applying telemedicine when compared with the control (including standard pain care or waitlist control) (Buhrman et al, 2016;Mariano et al, 2019). However, no therapeutic difference was found when compared to the active control (such as on-site therapies) (Mariano et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Some reviews have identified small to moderate reductions in pain, disability, and psychological symptoms in intervention groups applying telemedicine when compared with the control (including standard pain care or waitlist control) (Buhrman et al, 2016;Mariano et al, 2019). However, no therapeutic difference was found when compared to the active control (such as on-site therapies) (Mariano et al, 2019). Remotely delivered physical exercise interventions have also been proposed to reduce pain in patients as a substitute for the usual care (Adamse et al, 2018).…”
Section: Introductionmentioning
confidence: 99%